1994
DOI: 10.1055/s-2007-994565
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Genetic Disorders to Neonatal Mortality in a Regional Intensive Care Setting

Abstract: We examined the contribution of chromosomal abnormalities, mendelian disorders, and birth defects to mortality in a regional neonatal intensive care unit by medical record review of neonatal deaths in that unit. Of a total of 296 infant deaths during the 5-year period June 1986 to May 1991, 69 (23.3%) had a genetic disorder. By diagnostic category, 18.8% had a chromosomal abnormality, 10.1% had a mendelian condition, 42% had a single primary defect in development, and 29% had an unrecognized pattern of malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
(13 reference statements)
1
26
0
1
Order By: Relevance
“…For example, 57% of the lethal malformations in this study were multisystem anomalies, while similar analyses of causes of neonatal deaths from the USA found only 10 [4] and 29% [10] of lethal multiple malformations. Furthermore, 38 (68%) of 56 non-chromosomal multisystem malformations were due to recognized syndromes, while recognized syndromic malformations were very rarely seen in a similar study from neonatal intensive care in the USA [10] . The pattern of lethal malformation in this study is, however, similar to the general CA profi le previously reported for this community [11] .…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…For example, 57% of the lethal malformations in this study were multisystem anomalies, while similar analyses of causes of neonatal deaths from the USA found only 10 [4] and 29% [10] of lethal multiple malformations. Furthermore, 38 (68%) of 56 non-chromosomal multisystem malformations were due to recognized syndromes, while recognized syndromic malformations were very rarely seen in a similar study from neonatal intensive care in the USA [10] . The pattern of lethal malformation in this study is, however, similar to the general CA profi le previously reported for this community [11] .…”
Section: Discussionsupporting
confidence: 39%
“…Furthermore, most of the previous studies on genetic factors examined perinatal deaths [12][13][14][15] , and in the only previous study of neonatal deaths the rate of genetic evaluation was low [10] . In contrast, a clinical geneticist was involved in the evaluation of almost all the cases in the present investigation, which may have contributed to a more accurate assessment of genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although others have reported that congenital anomalies increase the risk of mortality in the NICU, these observations have not been incorporated in all severity-of-illness scores. Hudome et al 29 reported that 23% of deaths in an outborn children's hospital NICU had a chromosomal abnormality, Mendelian disorder or congenital malformation. Escobar et al 30 reported congenital anomalies in 40% of NICU deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have looked at the contribution of genetic conditions to mortality in a neonatal intensive care unit [Ling et al, 1991;Hudome et al, 1994] and a pediatric intensive care unit [Fitzpatrick et al, 1991;Cunniff et al, 1995]. Other studies investigated the role of genetic disorders in pediatric mortality and hospitalizations in specific regions [Roberts et al, 1970;Yoon et al, 1997].…”
Section: Introductionmentioning
confidence: 99%